1997
DOI: 10.1007/s001220050620
|View full text |Cite
|
Sign up to set email alerts
|

AFLP analysis of relationships among cassava and other Manihot species

Abstract: Despite the worldwide importance of cultivated cassava (M. esculenta Crantz) its origin and taxonomic relationships with other species in the genus have not been clearly established. We evaluated a representative sample of the crop's diversity and six wild taxa with AFLPs to estimate genetic relationships within the genus. Groupings of accessions of each species by data analysis corresponded largely with their previous taxonomic classifications. A mixed group, consisting of Manihot esculenta subsp. flabellifol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
86
1
3

Year Published

1999
1999
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(101 citation statements)
references
References 11 publications
(10 reference statements)
8
86
1
3
Order By: Relevance
“…Later, another Mesoamerican species, M. carthaginensis, was proposed as a wild relative [15,16]. Early studies with molecular markers did not clearly resolve the phylogeny of the genus [17,18]. However, they did identify a clear separation between the Mesoamerican and South American lineages, and found that cultivated manioc always grouped with South American species, suggesting that the crop was domesticated in South America.…”
Section: Maniocmentioning
confidence: 99%
“…Later, another Mesoamerican species, M. carthaginensis, was proposed as a wild relative [15,16]. Early studies with molecular markers did not clearly resolve the phylogeny of the genus [17,18]. However, they did identify a clear separation between the Mesoamerican and South American lineages, and found that cultivated manioc always grouped with South American species, suggesting that the crop was domesticated in South America.…”
Section: Maniocmentioning
confidence: 99%
“…More recently, wild populations of M. esculenta that are likely to be the crop's direct progenitors have been identified in South America (19,25). However, the evolutionary relationship between cassava and its conspecific wild relatives is only beginning to be examined (19,26,27), and there is continued speculation that the crop's origins may extend beyond M. esculenta to hybridizing Manihot species (26,27).…”
mentioning
confidence: 99%
“…flabellifolia (Pohl) Ciferri (see also ref. 27). This wild subspecies is found in forest patches in the transition zone between the cerrado (savanna scrub) vegetation of the Brazilian shield plateau and the lowland rainforest of the Amazon basin, where it grows as a clambering understory shrub or treelet.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…ciat.cgiar.org/urg/cassavacollection.do). Esta colección de Germoplasma ha sido evaluada, al menos parcialmente, mediante técnicas moleculares, a través del empleo de AFLP y microsatélites (Roa et al, 1997;Fregene et al, 2000) .…”
Section: Introductionunclassified